A hydrophobic antifouling surface coating on bioprosthetic heart valves for enhanced antithrombogenicity. Issue 5 (1st December 2021) - Li, Meiling; Zheng, Cheng; Zhang, Shumang; Wu, Binggang; Ding, Kailei; Huang, Xueyu; Lei, Yang; Wang, Yunbing
Abstract: Thrombosis is an important factor that causes the failure of artificial biological valves in addition to calcification and immune rejection. A hydrophobic antifouling surface can improve blood compatibility by reducing the absorption of protein. In this study, porcine pericardium was cross‐linked with glycidyl methacrylate, and carbon–carbon double bonds were introduced. Then, fluoride monomer was added so that the pericardial surface would become hydrophobic and antifouling. Fluoride modification changed the hydrophilicity of the pericardium surface, and the surface water contact angle increased from 84° to 143°. Compared with unmodified pericardium, the adsorption of bovine serum albumin and fibrinogen decreased by 93.1% and 85%, respectively, and the anti‐thrombogenicity was greatly enhanced. Abstract : Porcine pericardium was cross‐linked with glycidyl methacrylate, and carbon–carbon double bonds were introduced. Then, fluoride monomers were added for copolymerization, creating a hydrophobic and antifouling surface. The fluoride modification method described in this study can be widely applied to a variety of blood‐contacting materials, creating antifouling and antithrombogenic surfaces that can reduce the use of anticoagulant drugs and improve patients' quality of life.